Perilaku Multikultural dan Komunikasi Interkultural Siswa Sekolah Menengah Atas di Yogyakarta - Ary Purwantiningsih; Yos Sudarso; Kusnadi Kusnadi; Sidik Puryanto; Yunisca Nurmalisa (Universitas Negeri Malang, 2025)
The purpose of this study is to analyze the multicultural behavior and intercultural communication of students based on their ethnic background and gender differences. This study uses a quantitative and qualitative approach with survey methods and in-depth interviews. The results of the study show that the multicultural behavior and intercultural communication of high school students in Yogyakarta are in the positive category. The multicultural behavior of Javanese students is directed towards cultural insight and flexibility, while non-Javanese students are more dominant in communication, cultural values, and cultural awareness. The multicultural behavior of female students is directed towards cultural insight, communication, cultural values, and cultural awareness, while male students are more dominant in flexibility. The intercultural communication of Javanese students tends to be more stable in terms of communication style and competence, while non-Javanese students have a higher intensity because they are able to actively practice cross-cultural communication. Intercultural communication carried out by female students in all dimensions tends to be higher than that of male students.